Introdução hermenêutica ao positivismo jurídico inclusivo: a teoria do Direito de Matthew Kramer - Campis, Francisco Kliemann a (Universidade do Vale do Rio dos Sinos, 2023)
This dissertation aims to investigate Matthew Kramer's theoretical proposal within Legal Theory. Through an exploration of the main assumptions and implications of the history of Legal Positivism, the research seeks to position Kramer's Inclusive Legal Positivism. To achieve this goal, and based on a bibliographic review conducted under the phenomenological method (underlying the tradition of Legal Hermeneutics Critique by Lenio Streck), the study, structured in three chapters, addresses the following topics: in the first chapter, (i) Some introductory notions and important considerations regarding the discussion of Legal Positivism, the historical context of the emergence of legal positivism in the classical common law theory, and (ii) the theory of Edward Coke and subsequent Positivists who shaped the AngloSaxon tradition: Hobbes, Bentham, and Austin; in the second chapter, the investigation turns to (i) Herbert Hart and the transition from a command theory to a normative-descriptive theory and the development of Legal Positivism within the philosophy of language; (ii) then introduces Ronald Dworkin's "general attack" on Legal Positivism and its hermeneutic counterpoints that led to a division within Legal Positivism; finally, in the third chapter, I aim to demonstrate (i) how Dworkin's "general attack" caused a division in legal positivism, (ii) what Inclusive Legal Positivism entails, and (iii) the arguments put forth by Matthew Kramer supporting his view of Inclusive Legal Positivism and its connection between Law and morality. In this sense, the conclusion is that Kramer offers a novel and highly original approach to Legal Positivism and its relationship with morality, addressing many of Dworkin's questions but proving inadequate in interpreting Law as an interpretive rather than criterial phenomenon, a problem shared by all legal positivists.

Diese Dissertation hat zum Hauptziel, die theoretischen Ansätze von Matthew Kramer in der Rechtstheorie zu untersuchen. Durch die Aufdeckung der wichtigsten Annahmen und Implikationen der Geschichte des Rechtspositivismus beabsichtigt die Forschung, den inklusiven Rechtspositivismus von Kramer zu verorten. Zu diesem Zweck und auf Grundlage einer bibliografischen Recherche, die unter der "phänomenologischen Methode" (im Kontext der Tradition der Rechtshermeneutik von Lenio Streck) durchgeführt wurde, behandelt die Studie in drei Kapiteln die folgenden Themen: Im ersten Kapitel werden (i) einige einführende Begriffe und wichtige Überlegungen zur Diskussion des Rechtspositivismus erörtert, der historische Kontext des Aufkommens des Rechtspositivismus im Rahmen der klassischen Common-Law-Theorie und (ii) die Theorie von Edward Coke sowie die Positivisten, die ihm folgten und die anglo-sächsische Tradition prägten: Hobbes, Bentham und Austin; Im zweiten Kapitel wendet sich die Untersuchung (i) Herbert Hart und dem Übergang von einer Befehlstheorie zu einer normativ-deskriptiven Theorie zu sowie der Entwicklung des Rechtspositivismus innerhalb der Sprachphilosophie zu; (ii) führt dann den "generellen Angriff" von Ronald Dworkin gegen den Rechtspositivismus ein und seine hermeneutischen Gegenpunkte, die zu einer Spaltung im Rechtspositivismus führten; schließlich zielt das dritte Kapitel darauf ab zu zeigen, (i) wie der "generelle Angriff" von Dworkin eine Spaltung im Rechtspositivismus verursachte, (ii) was der inklusive Rechtspositivismus beinhaltet, und (iii) die Argumente, die Matthew Kramer für seine Sicht des inklusiven Rechtspositivismus und dessen Verbindung zwischen Recht und Moral vorbringt. In diesem Sinne kommt die Schlussfolgerung zu dem Ergebnis, dass Kramer einen neuartigen und äußerst originellen Ansatz zum Rechtspositivismus und seiner Beziehung zur Moral bietet, viele der Fragen von Dworkin anspricht, aber sich als unzureichend bei der Interpretation des Rechts als Phänomen der Interpretation und nicht der Kriterien herausstellt, ein Problem, das alle Rechtspositivisten teilen.

Cette thèse a pour objectif principal d'investiguer la proposition théorique de Matthew Kramer dans la Théorie du Droit. En révélant les principales hypothèses et implications de l'histoire du Positivisme Juridique, la recherche vise à situer le Positivisme Juridique Inclusif de Kramer. À cette fin, et à partir d'une recherche bibliographique menée selon la méthode phénoménologique (sous-jacente à la tradition de la Critique Herméneutique du Droit de Lenio Streck), l'étude, structurée en trois chapitres, aborde les thèmes suivants : dans le premier chapitre, (i) Certaines notions introductives et importantes considérations sur la discussion du Positivisme Juridique, le contexte historique de l'émergence du positivisme juridique dans la théorie classique de la common law, et (ii) la théorie d'Edward Coke et des positivistes qui lui ont succédé et ont façonné la tradition anglo-saxonne : Hobbes, Bentham et Austin ; dans le deuxième chapitre, l'investigation se tourne vers (i) Herbert Hart et le passage d'une théorie du commandement à une théorie normativedescriptive, et le développement du Positivisme Juridique dans la philosophie du langage ; (ii) puis introduit l' "attaque générale" de Ronald Dworkin contre le Positivisme Juridique et ses contrepoints herméneutiques qui ont conduit à une division au sein du Positivisme Juridique ; enfin, dans le troisième chapitre, j'essaie de démontrer (i) comment l' "attaque générale" de Dworkin a provoqué une division dans le positivisme juridique, (ii) ce qu'implique le Positivisme Juridique Inclusif, et (iii) les arguments avancés par Matthew Kramer étayant sa vision du Positivisme Juridique Inclusif et sa relation entre le Droit et la morale. Dans ce sens, la conclusion est que Kramer propose une approche novatrice et très originale du Positivisme Juridique et de sa relation avec la morale, répondant à de nombreuses questions de Dworkin, mais se révélant insuffisante dans l'interprétation du Droit en tant que phénomène interprétatif plutôt que critérialiste, un problème partagé par tous les positivistes juridiques.
Keywords: Jurisprudence; Matthew Kramer; Positivismo jurídico; Positivismo Jurídico Inclusivo; Hermenêutica; Legal positivism; Inclusive Legal Positivism; Hermeneutics; Rechtstheorie; Rechtspositivismus; Inklusiver Rechtspositivismus; Hermeneutik; Théorie juridique; Positivisme juridique; Positivisme Juridique Inclusif; Herméneutique; ACCNPQ::Ciências Sociais Aplicadas::Direito